Casuarina Cunninghamiana Miq. (River Sheoak) in Florida and Its Potential as a Windbreak Plant for Citrus Groves - William S. Castle; Kenneth A. Langeland; Donald L. Rockwood (EDIS, 2012)
This review was undertaken to compile pertinent information and provide a historical perspective for environmentalists, biologists, scientists, and other interested parties regarding the Casuarina species in Florida, which are presently classified as invasive and illegal to possess or propagate. This revised 10-page fact sheet was written by William S. Castle, with minor revisions by Kenneth A Langeland and Donald L. Rockwood. Published by the UF Horticultural Sciences Department, October 2012.